Access to Study Abroad forStudents at Rural Community Colleges (Comparative & International Education Series, 2021)
While there has been limited research documenting the study abroad experiences of community college students, very few studies have focused on how rural two-year colleges use study abroad to increase student knowledge of international affairs, boost access to valuable cross-cultural experiences, and promote cultural awareness, professional growth, and academic success. For this study, the researchers utilized a qualitative survey, interviews leaders of community college short-term study abroad programs, and document analysis with the goal of identifying practices to develop sustainable short-term study abroad programs at rural community colleges. The findings indicated that rural community college leaders should enhance faculty motivation and acknowledge and encourage the efforts of study abroad leaders.